2014
DOI: 10.1186/s12863-014-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for somatic cell score in Valdostana Red Pied cattle breed using pooled DNA

Abstract: BackgroundMastitis is a major disease of dairy cattle occurring in response to environmental exposure to infective agents with a great economic impact on dairy industry. Somatic cell count (SCC) and its log transformation in somatic cell score (SCS) are traits that have been used as indirect measures of resistance to mastitis for decades in selective breeding. A selective DNA pooling (SDP) approach was applied to identify Quantitative Trait Loci (QTL) for SCS in Valdostana Red Pied cattle using the Illumina Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 32 publications
6
28
0
1
Order By: Relevance
“…Other identified genes in our current study are involved in somatic cell score and meat quality traits, such as GRIN2B (Wu et al. 2014) and PLXNA4 (Strillacci et al. 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Other identified genes in our current study are involved in somatic cell score and meat quality traits, such as GRIN2B (Wu et al. 2014) and PLXNA4 (Strillacci et al. 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This study also identified ACSL1 associated with the milk fatty acid traits (Li et al 2014) and supported by other studies (Widmann et al 2011;Gao et al 2013;Weber et al 2013). Other identified genes in our current study are involved in somatic cell score and meat quality traits, such as GRIN2B (Wu et al 2014) and PLXNA4 (Strillacci et al 2014). …”
Section: Strs Overlap With Regions Under Selection Predicted Based Onmentioning
confidence: 68%
“…Strillacci et al . () reported a list of the chromosome regions (including IGF1R region) defined by at least three SNPs that are strongly associated with mastitis resistance and somatic cell score. There are also manuscripts in which there was no effect of IGF1R gene on milk traits (Jiang et al .…”
Section: Discussionmentioning
confidence: 99%
“…IGF1R was also shown to control innate immunity in mammals and served as a potential tool in mastitis prevention (Sugimoto & Sugimoto 2012). Strillacci et al (2014) reported a list of the chromosome regions (including IGF1R region) defined by at least three SNPs that are strongly associated with mastitis resistance and somatic cell score. There are also manuscripts in which there was no effect of IGF1R gene on milk traits (Jiang et al 2010;Meredith et al 2012).…”
Section: Discussionmentioning
confidence: 99%